A Preliminary Assessment of Power Savings by Flettner Rotors Installed on a Cargo Ship (MIST International Journal of Science and Technology, 2025)
In response to increasingly stringent environmental regulations by the International Maritime Organization (IMO), this study presents a preliminary assessment of Flettner rotors as a viable wind-assisted propulsion system for cargo ships. Using RANS-based Computational Fluid Dynamics (CFD), the aerodynamic performance of various rotor configurations is evaluated under different wind speeds, spin ratios, and angles of attack. Initially, an isolated 2D and 3D rotor at model scale are simulated for various operating conditions. A grid convergence study is conducted as part of the CFD results verification process. A cargo ship fitted with Flettner rotors is simulated to compute resistance and to evaluate rotor to rotor interaction. The obtained results and analyses demonstrate that, under optimal conditions, Flettner rotors have the potential to reduce fuel consumption and emissions by around 20%, significantly enhancing propulsive efficiency.MIJST, Vol. 13, June 2025 : 73-82DOI: https://doi.org/10.47981/j.mijst.13(01)2025.508(73-82)